Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.bcp.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Copper influx transporter 1 is required for FGF, PDGF and EGF-induced MAPK signaling

Abstract: Copper transporter 1 (CTR1) is the major copper (Cu) influx transporter in mammalian cells. We report here that CTR1 is required for the activation of signaling to the MAPK pathway by the ligands of three major receptor tyrosine kinases (RTK) including FGF, PDGF and EGF. Induction of Erk1/2 phosphorylation was compared in isogenic wild type CTR1+/+ and CTR1−/− cells. Whereas all three ligands increased pErk1/2 in the CTR1+/+ cells, they failed to do this in CTR1−/− cells. While FGF did not enhance the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 36 publications
1
42
1
Order By: Relevance
“…Overexpression of Akt1 enhanced survival of grafted human NSCs transplanted into mouse brains with ICH induced by striatal collagenase injection, as demonstrated by Lee et al 10 Reactive oxygen species contributed to enhanced Akt activity in NSCs, 32,33 and an increase in Akt activity was induced by intracellular H 2 O 2 converted from superoxide by SOD1. 36 Although pAkt expression increased in the SOD1 Tg NSCs compared with the WT NSCs after exposure to H 2 O 2 , there was no difference in pAkt expression between SOD1 Tg NSCs and WT NSCs after exposure to Hb in this study. An earlier report by our group showed that cortical neurons that overexpress SOD1 had a tolerance against ischemic insults via upregulation of Akt signaling.…”
Section: Discussioncontrasting
confidence: 54%
“…Overexpression of Akt1 enhanced survival of grafted human NSCs transplanted into mouse brains with ICH induced by striatal collagenase injection, as demonstrated by Lee et al 10 Reactive oxygen species contributed to enhanced Akt activity in NSCs, 32,33 and an increase in Akt activity was induced by intracellular H 2 O 2 converted from superoxide by SOD1. 36 Although pAkt expression increased in the SOD1 Tg NSCs compared with the WT NSCs after exposure to H 2 O 2 , there was no difference in pAkt expression between SOD1 Tg NSCs and WT NSCs after exposure to Hb in this study. An earlier report by our group showed that cortical neurons that overexpress SOD1 had a tolerance against ischemic insults via upregulation of Akt signaling.…”
Section: Discussioncontrasting
confidence: 54%
“…After immunoprecipitation of CTR1 from the HEK293 FLP-In T-Rex cells with anti-FLAG antibody, crosslinked binding partners were selectively released by reduction with β-mercaptoethanol which resulted in an extremely efficient recovery with exceptionally low background. Proteomic analysis of the released trypsin-digested proteins identified insulin receptor substrate 4 (IRS-4) and this was considered of interest because IRS proteins mediate a variety of biological effects downstream of the insulin and insulin-like growth factor 1 (IGF-1) receptors, and we had previously demonstrated that CTR1 plays an important role in regulating signaling from receptor tyrosine kinases [36]. The IRS-4 peptides identified by mass spectrometry are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, this domain contains several motifs that are of interest to a potential scaffold role of CTR1 that facilitates the binding of other proteins. In Xenopus CTR1 is important for signaling during embryonic development [37] and recent studies have shown that it is essential for signaling from multiple receptor tyrosine kinases in mouse cells [36,38]. Molecular modeling suggests that the intracellular loop is a likely site for the docking of proteins that participate in this pathway [12].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of proteasomal activity enhances delivery of cDDP in ovarian carcinoma cells, and promises significant clinical potential, but its basis is also not yet clear (Jandial et al, 2009). The recent observation that copper is involved in growth factor kinase cycling in tumor cells introduces a new complexity (Tsai et al, 2012), and recent studies suggest important interactions between ATP7A, hCTR1, Atox1, and the platelet-derived growth factor receptor in cell activation (Ashino et al, 2010). (A) cDDP-sensitive (A2780) cells were transiently transfected with siRNA duplexes against CTR1 or siRNA negative control in Opti-MEM medium.…”
Section: Cisplatin Entry Into Human Cellsmentioning
confidence: 99%